Influence of Ambient Perfumes on Consumer Spending Behaviour : A Study Among Apparel Shoppers in an Indian Setting - Joji Alex, N.; Menon, Parvathy (Indian Journal of Marketing, 2018)
The objective of this study was to externally validate the two competing models, that is, emotion-cognition model and the cognition-emotion model in the Indian context. This helps to substantiate the research study conducted by Chebat and Michon (2003), which concluded that the cognition - emotion model better explains the influence of ambient perfume. The proposed competing models were tested in a mall setting with approximately 200 shoppers in a popular retail store selling branded apparel located in South India. Results: In the emotion-cognition model, in the occurrence of perfumes, pleasure influenced shopper spending (dependent outcome) through mall atmosphere and product quality (both mediates), and the model cannot be fully substantiated because the average scores of the both groups across these variables were not statistically significant. To summarize the results of the cognition - emotion model, occurrence of perfume created an overall influence of mall atmosphere on product quality, and the overall correlation of pleasure on consumer spending (purchase) was stronger in the occurrence of perfume. Moreover, the consumer spending in the occurrence of perfumes was 13% more. As per the results of this experimental study, both the 'emotion based' and the 'perception based' models reasonably explained the effect of perfumes on consumer spending. Originality/Research Contribution: This work was done in an external setting using real shopping environment and helped to compare the Western culture based results to Indian settings.